A genome‐wide association study platform built on iPlant cyber‐infrastructure. (6th March 2014) - Wang, Liya; Ware, Doreen; Lushbough, Carol; Merchant, Nirav; Stein, Lincoln; Wilkins‐Diehr, Nancy; Gesing, Sandra; Kiss, Tamas
Summary We demonstrate a flexible genome‐wide association study platform built upon the iPlant Collaborative Cyber‐infrastructure. The platform supports big data management, sharing, and large‐scale study of both genotype and phenotype data on clusters. End users can add their own analysis tools and create customized analysis workflows through the graphical user interfaces in both iPlant Discovery Environment and BioExtract server. Copyright © 2014 John Wiley & Sons, Ltd.